Relationship Between Sustainability Report, Financial Performance, and Ownership Structure: Research on The Turkish Banking Sector - Mesut Doğan; Mustafa Kevser (Istanbul Business Research (IBR), 2021)
The financial statements of companies have been evaluated in financial performance analysis for many years. However, today, investors and business stakeholders, who want to invest in businesses, demand not only the information presented in financial statements, but also non-financial information to see future status and test whether it have a sustainable structure. In this context, the reporting of information on the economic, social, and environmental dimensions of businesses is possible through sustainability reporting. The purpose of this study is to reveal the sustainability scores of banks operating in the Turkish Banking sector. Another aim of the study is to determine the relationship between the sustainability score of banks, financial performance indicators, and ownership structure. In the study, the compliance scores of banks along with a sustainability report determined the framework of criteria for sustainability reports standardized by the GRI. From 2013-2018, the data of 10 banks that published sustainability reports in the Turkish Banking Sector were analysed. According to the results obtained from the research, the sustainability score of banks was not effective based on their financial performance. On the other hand, an increase in the shares of the largest shareholder capital caused a decrease in the sustainability scores of banks.
Keywords: 650; GRI; Sustainability reporting; Financial performance; Ownership structure; Banking